Effectiveness of an educational program to control modifiable risk factors for breast cancer - Álvarez-Perulena, Lourdes (2023)
Worldwide, breast cancer represents the most frequent tumor among women. A pre-experimental study was carried out, with the use of quantitative and qualitative methods in the family doctor’s offi ce 31, of the 50th Anniversary Polyclinic of Manicaragua, Cuba from January 2018 to June 2021, to determine the eff ectiveness of an educational program for the control of modifi able risk factors of breast cancer, in women of the clinic 31 of Manicaragua. From a population of 128 women aged 25 to 75 years and over, a sample of 25 women was selected according to non-probabilistic sampling by criteria. Descriptive and inferential statistics were used. Th e predominant toxic habit in women was smoking in 80% of the studied sample and after the implementation of the educational program, it decreased to 32%. Th e level of knowledge about risk factors was raised to a good level in 80% of the sample and 76% managed to correctly perform the breast self-examination. Th e eff ectiveness of the educational program for the control of modifi able risk factors for breast cancer, in women from clinic 31 of Manicaragua, can be evaluated as favorable since it raised the level of knowledge about modifi able risk factors and correct performance of self-examination of breast cancer. breast, the practice of addictive substances decreased signifi cantly and the women showed satisfaction with the intervention.